Pengaruh Waktu Dan Temperatur Pelindian Terhadap Hasil Ekstraksi Nikel Laterit Menggunakan H2SO4 Pada Tekanan Atmosfer - Malik, Yulianti; Hardiono, Rizky; Septiawan, Muh. Rdwan (REACTOR: Journal of Research on Chemistry and Engineering, 2025)
The rising demand for nickel in electric vehicle batteries drives the adoption of hydrometallurgical processing, notably Atmospheric Leaching (AL) and High-Pressure Acid Leaching (HPAL), primarily using acid solutions like sulfuric acid for Ni extraction. Although AL offers lower operating costs and simpler equipment, it is typically challenged by high levels of Fe impurities and elevated acid consumption compared to HPAL. To address these limitations, this research investigated optimizing AL by manipulating key process parameters: time and temperature. The study focused on lateritic nickel ore leaching using 0.8 M sulfuric acid, maintaining a solid-to-liquid (S/L) ratio of 20% and a stirring speed of 350 rpm. Experiments were conducted across temperatures of 75, 85, and 95oC and durations from 2 to 8 hours. The optimal result was achieved at 95oC for 8 hours, yielding the highest Ni extraction of 55.81% and the lowest total acid consumption of 1399.45 kg/ton of ore. This indicates that increased temperature and duration accelerate the Ni reaction rate with the sulfuric acid. The extraction of Fe rapid initially decreased significantly over time due to saturation, which directly contributed to the desirable reduction in overall acid consumption.